På språng efter förnuftets gränser: sinnesrus och idealistisk skönhet: Musikkritiker om ”seriös” och ”banal” musik i Helsingfors på 1920- och 1930-talen - Sarjala, Jukka (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1992)
The differentiation of music into the categories “serious” and “banal” were central forthe music critics in Helsinki, Finland during the 1920s and -30s. Which criteria qualified some works of music as Great Art, while others were drawn down to the banal? The discussion was not primarily philosophical, but concerned the defence of the aesthetic and social status of art music in a time marked by the breaking of bonds with old traditions. The news paper critics tried to manifest the nature of art music and determine which music was worthy of carrying this name. At the beginning of the 20s, most critics were professional musicians: the music critic became a way of strengthening the group identity among the musicians of the city. Therefore, polemic discussions were rare, the reviews were not so much discussions as a continuously repeated stating of certain norms and values. The reviews made the readers believe that an established concert institution henceforth was a necessary and important phenomenon and that the professional musicians were worthy of the audience’s interest and esteem. There were, however, a social break during the period; it became possible also for persons from lower social strata to rise to the position of composer. The influences from Germany and the classicist-romantic tradition were massive on the Finnish critics during the period before the first world war, and this tradition was never questioned. The core of the musical canon consisted of the symphonic production of Beethoven. There was no real discussion of interpretations — the reviews were constructed from a repertoire of repeated phrases and functioned as news. An important dichotomy was drawn between outer means of influence and inner qualities of beauty. The outer effects were seen as expressions of sensuality and of secondary worth, they threatened the autonomous character of the music. The important values of beauty were spiritual, beyond the empirical world. The metaphysical nature of music strengthened the ritualistic character of the concert culture. The more the critics needed to motivate the autonomy of art, the stronger were the attacks on the banal, which were seen as a lack of individuality. The individuality was manifested through means of the interval structure and the form creating nature of the tonal system, while the rhythm appealed to the body, and were therefore thought to make the music banal. This critics also discussed jazz, which during the -20s meant all types of urban popular music and culture. Some critics hoped for a synthesis between jazz and art music, but these hopes seems to have disappeared during the -30s. When, however, jazz finally was established as a form of popular music, it did no longer threaten the status and the normative values of art music, and therefore adaptions of jazz elements into art music gradually became more easily accepted.